Influence of designer diet and holy basil (Ocimum sanctum) leaves on yolk colour, yolk carotenoid, and immunity status of layers - KIRUBAKARAN, A (The Indian Journal of Animal Sciences, 2022)
A biological experiment of six weeks duration, followed by several laboratory investigations was carried out to study the effect of designer layer mash (DLM) containing full fat flaxseed, oil rich sardine fish, holy basil leaf meal (BLM), vitamin E and organic selenium (Sel-plex), on yolk colour, carotenoid and immune status of layers. Both designer diet and BLM had significantly improved the yolk colour and pigment levels. They also exhibited a synergistic effect. The DLM had significantly increased the vitamin E and selenium levels in the egg; but BLM had no such effect. The immune status of the layers, expressed as Immunoglobulin IgY and HI titre, indicated that both designer diet as well as the BLM had significantly improved the IgY levels and HI titre.